Settlement and crusade in the thirteenth century
1 online resource.
Keywords: "Settlement and Crusade in the Thirteenth Century sheds new light on formerly less explored aspects of the crusading movement and the Latin East during the thirteenth century. In commemoration of the 800th anniversary of the construction of 'Atlit Castle, a significant section of this volume is dedicated to the fortification, which was one of the most impressive built in the Latin East. Scholarly debate has centred on the reasons behind the construction of the castle, its role in the defence of the Kingdom of Jerusalem during the thirteenth century, and its significance for the Templar order. The studies in this volume shed new light on diverse aspects of the site, including its cemetery and the surveys conducted there. Further chapters examine Cyprus during the thirteenth century, which, under the Lusignan dynasty, was an important centre of Latin settlement in the East, and a major trade centre. These articles present new contributions regarding the complex visual culture which developed on the island, the role of the mendicant orders in Cyprus, and settlement patterns. Adopting a multidisciplinary approach, this book will be of interest to scholars and students of the medieval period, as well as those interested in the crusades, archaeology, material culture, and art history"--